2021
DOI: 10.1002/cam4.4159
|View full text |Cite
|
Sign up to set email alerts
|

DYRK1A activates NFATC1 to increase glioblastoma migration

Abstract: Glioma is the most common brain cancer, and high-grade gliomas, including glioblastoma multiforme (GBM), are the most aggressive types of glioma. 1 The current standard treatment for GBM involves surgical resection followed by the administration of an alkylating agent, temozolomide, both concurrent with and after radiotherapy. Bevacizumab is administered as a second-line treatment after relapse. 2,3 However, GBM is resistant to chemotherapy and radiotherapy, with a median patient survival time of approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
(127 reference statements)
0
8
0
Order By: Relevance
“…Several studies have indicated that DYRK1A acts as a tumour suppressor gene, while others have highlighted its pro-oncogenic activity [ 8 ]. For instance, DYRK1A could activate NFATC1 to increase the migration ability of glioblastoma cells, while it could play an important role in maintaining cancer stemness in oral squamous cell carcinoma [ 15 , 33 ]. In contrast, another study showed that DYRK1A could act as a tumour suppressor by downregulating c-Myc in acute myeloid leukaemia cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have indicated that DYRK1A acts as a tumour suppressor gene, while others have highlighted its pro-oncogenic activity [ 8 ]. For instance, DYRK1A could activate NFATC1 to increase the migration ability of glioblastoma cells, while it could play an important role in maintaining cancer stemness in oral squamous cell carcinoma [ 15 , 33 ]. In contrast, another study showed that DYRK1A could act as a tumour suppressor by downregulating c-Myc in acute myeloid leukaemia cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the binding sites of between DYRK1A and TSC1 should be further determined. It has been reported that DYRK1A increases the stability of its substrates, such as NFATC1, by phosphorylating and interfering with their ubiquitin-mediated proteasomal degradation [ 15 ]. Our data indicated that DYRK1A enhanced the expression of TSC1 and that TSC1 enhanced the expression of DYRK1A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the literature supporting the link between DYRK1A inhibition and induction of glioblastoma cell death , (see the review in ref ) and given the relative brain permeability of Leucettinib-21 ( 4 ) (unpublished results), we tested this compound and its kinase-inactive isomer on patient-derived, Temozolomide-resistant glioblastoma stem-like cells (GSCs) (Figure ). Cells were exposed for 48 h to a range of concentrations of both compounds, and cell death was assessed using the Cell Titer-Glo luminescent ATP assay.…”
Section: Resultsmentioning
confidence: 99%
“…The validation was approved by the Ethics Committee of Qilu Hospital, and all patients provided informed consent. IHC staining was performed as previously described 30 . Serial sections of formalin-fixed tissues were deparaffinized, rehydrated, immersed in citrate buffer (pH 6.0), and microwaved for 15 min to retrieve antigens.…”
Section: Methodsmentioning
confidence: 99%